2019
DOI: 10.1177/0300060519865629
|View full text |Cite
|
Sign up to set email alerts
|

Resection of mesothelial cyst of uterine round ligament by laparoscopic transabdominal preperitoneal procedure alone or combined with open surgery

Abstract: Objective: Surgical treatment of a mesothelial cyst of the uterine round ligament (MCURL), an uncommon entity, has been rarely documented. In this article, we present our experience with excision of MCURLs. Methods: The records of all female patients undergoing surgical removal of a groin mass in our department from March 2013 to November 2018 were retrospectively reviewed. Demographic information, clinical data, and follow-up outcomes were collected and analyzed. Results: Among 298 women who underwent groin h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In this study, the incidence of MCURL was 12.9% (74/572). As reported in previous small cohort studies, the incidence of MCURL was 2.2% to 5.7% 21,22 . Chen et al 21 found that MCURL was mostly found in middle-aged women and was more common on the right side.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In this study, the incidence of MCURL was 12.9% (74/572). As reported in previous small cohort studies, the incidence of MCURL was 2.2% to 5.7% 21,22 . Chen et al 21 found that MCURL was mostly found in middle-aged women and was more common on the right side.…”
Section: Discussionmentioning
confidence: 67%
“…As reported in previous small cohort studies, the incidence of MCURL was 2.2% to 5.7%. 21,22 Chen et al 21 found that MCURL was mostly found in middle-aged women and was more common on the right side. In our study, by comparing patients of different ages with MCURL, we found that the incidence of MCURL was correlated with patient age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations